Legal Problems In one person company Limited liability - عبد, اندلس حامد (Journal of Legal Sciences, 2020)
The emergence of one-person company as a necessary to cope with the needs of the market and the result of economic development and trade activities and the need for the market for the emergence of many companies and increase the opportunity to work and eliminate unemployment. One person is a turning point because it will encourage many owners of economic activities to establish these companies properly legally, which has an impact on improving the economy in the indicators of global competitiveness and in order to reduce the sham companies, and the development of business Irrigation and investment activities practiced by the various companies have emerged the need for this company, has been e-commerce and its role in small and medium-sized enterprises in the impact of the emergence of this idea despite the absence of an independent legal organization to clarify some of the legal aspects related to this company. It is through this company that the responsibility of the sole partner in the company of one person is determined in a manner that corresponds to his commercial responsibility and his own funds to avoid mixing his financial liabilities with the funds allocated for trade. Credit as well as the absence of the principle of contractual relationship in the company of one person, noting the difference of the company of one person from the rest of the companies as they are new developments in the field of companies and what it requires to work to create a balance between the interest of the only partner and the interest of creditors of the company, as it is The existence of this company is a step to facilitate the conduct of business, which has emerged following the development of economic life and the need to keep pace with progress, one person limited liability company attracts owners of small and medium enterprises have touched the Iraqi legislator resort to some owners of companies to form a limited liability company as a way to benefit and get huge profits They are in fact fake companies, where partners are just names that have no role but to fulfill the legal form of the company, it is the primary partner who holds the entire company apparently bear the partnership, while in reality it is a company run by one person embodied negatives When there is a loss in the company, the other funds of the entrepreneur are safe from the claim of creditors and in order to eliminate the sham of these companies and protect dealers with them came the Iraqi legislator this company as an urgent need to keep abreast of developments in the world of trade, so this trend is true to eliminate the fake companies And determine the responsibility of the owner of the company before others.